Accounting Information System Application Development on MSMEs in Kerinjing Village - Arista Hakiki; Yusnaini; Aryanto (Sriwijaya Accounting Community Services, 2022)
Accounting Information Systems can be used on all types and scales of business, both large scale and Micro, Small and Medium Enterprises (MSMEs). The phenomenon in the field shows that most MSMEs think that accounting information systems are not needed in managing business ventures and even seem expensive and complex. Based on this view, it is necessary to develop an accounting information system application for MSMEs. It is hoped that this development can provide solutions to problems related to the use of MSME accounting information system applications, especially in Kerinjing Village. Assistance activities for implementing accounting information system applications for MSMEs in Kerinjing Village, Ogan Ilir can be useful in contributing to the development of Micro, Small and Medium Enterprises business in Kerinjing Ogan Ilir Village, especially in optimizing the performance of accounting information systems. The output of this activity is an accounting information system application that can be implemented by MSMEs in Kerinjing Village, Ogan Ilir